Dynamic common correlated effects of trade openness, FDI, and institutional performance on environmental quality: evidence from OIC countries - Ali, Sajid; Yusop, Zulkornain; Kaliappan, Shivee Ranjanee; Chin, Lee (Springer, 2020)
The study aims to address the dynamic common correlated effects of trade openness, FDI, and institutional performance on environmental quality in OIC countries. Mostly, pollutants like CO2 and SO2 emissions are considered as the environmental indicators. However, for this study, we have selected ecological footprint as the indicator of environmental quality. The new econometric approach Dynamic Common Correlated Effects (DCCE) by Chudik and Pesaran (2015) has been used to measure the cross-sectional dependence among cross-sectional units. Results confirm that previous techniques for long panel data, like MG and PMG, give ambiguous outcomes in the presence of cross-sectional dependence. According to DCCE estimation, trade openness, FDI, and urbanization have a positive and significant relationship with ecological footprint while a significant and negative association is found between institutional performance and ecological footprint. The OIC countries must encourage green technology, clean production, and improved institutions for sustainable development and better environmental quality.